Family Matters: Immigrant Women’s Activism in Ontario and British Columbia, 1960s -1980s - Little, Margaret; Marks, Lynne Sorrel; Beck, Marin; Paszat, Emma; Tom, Liza (Atlantis, 2020)
This article uses oral history interviews to explore the ways in which different attitudes towards family and motherhood could create major tensions between mainstream feminists and immigrant women’s activists in Ontario and British Columbia between the 1960s and the 1980s.  Immigrant women’s belief in the value of the family did not prevent immigrant women from going out to work to help support their families or accessing daycare and women’s shelters, hard fought benefits of the women’s movement.  However, these women demanded access to job training, English language classes, childcare, and women’s shelters on their own terms, in ways that minimized the racism they faced, respected religious and cultural values, and respected the fact that the heterosexual family remained an important resource for the majority of immigrant women. Immigrant women activists were less likely to accept a purely gender-based analysis than mainstream feminists. They often sought to work with men in their own communities, even in dealing with violence against women. And issues of violence and of reproductive rights often could not be understood only within the boundaries of Canada. For immigrant women violence against women was often analyzed in relation to political violence in their homelands, while demands for fully realized reproductive rights drew on experiences of coercion both in Canada and transnationally.